Detection of a de novo duplication of 1q32-qter by fluorescence in situ hybridisation in a boy with multiple malformations: further delineation of the trisomy 1q syndrome. Issue 4 (April 1997) - Duba, H C; Erdel, M; Löffler, J; Bereuther, L; Fischer, H; Utermann, B; Utermann, G
Abstract : We report a dysmorphic boy with a de novo partial trisomy 1q. The boy has microcephaly, bilateral cleft lip and palate, low set and dysmorphic ears, brain anomalies, pulmonary stenosis, duodenal obstruction, dysplastic kidneys, and bifid thumbs. The trisomic segment 1q32-qter is duplicated with an inverted insertion at 1p36.3. The aberration was initially detected at amniocentesis and confirmed and defined by GTG banding, chromosome microdissection, and FISH on postnatal blood samples. The parents had normal karyotypes. De novo partial duplications of chromosome 1q have rarely been reported. Comparison of our patient with other published pure trisomy 1q cases showed similarities which allowed the further delineation of the trisomy 1q syndrome.